2000
DOI: 10.1002/(sici)1096-9861(20000522)421:1<80::aid-cne5>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and immunocytochemical localization of a cyclic nucleotide-gated channel ?-subunit to all cone photoreceptors in the mouse retina

Abstract: Cyclic nucleotide-gated channels (CNGC) are ligand-gated ion channels that open and close in response to changes in the intracellular concentration of the second messengers, 3′,5′-cyclic adenosine monophosphate and 3′,5′-cyclic guanosine monophosphate. Most notably, they transduce the chemical signal produced by the absorption of light in photoreceptors into a membrane potential change, which is then transmitted to the ascending visual pathway. CNGCs have also been implicated in the signal transduction of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Rod and cone photoreceptor CNG channels are localized to the plasma membrane of the outer segment and play a pivotal role in phototransduction (6,7). Structurally, CNG channels belong to the superfamily of voltage-gated ion channels and comprise two structurally related subunit types, the A and B subunits: CNGA1/B1 in rods and CNGA3/B3 in cones.…”
Section: Introductionmentioning
confidence: 99%
“…Rod and cone photoreceptor CNG channels are localized to the plasma membrane of the outer segment and play a pivotal role in phototransduction (6,7). Structurally, CNG channels belong to the superfamily of voltage-gated ion channels and comprise two structurally related subunit types, the A and B subunits: CNGA1/B1 in rods and CNGA3/B3 in cones.…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily because of the difficulty of investigating the cone system in a rod-dominant mammalian retina, as cones comprise only 3-5% of the total photoreceptor population. Although CNGA3 gene has been cloned in human, bovine, mouse, rat, chicken, and striped bass (Bonigk et al 1993;Biel et al 1994;Weyand et al 1994;Misaka et al 1997;Wissinger et al 1997;Hirano et al 2000;Paillart et al 2006) and CNGB3 gene has been cloned in human, canine, mouse, and striped bass (Gerstner et al 2000;Kohl et al 2000;Sidjanin et al 2002;Paillart et al 2006), the biochemical components of native cone CNG channel have never been determined. Studies using heterologous expression system (Peng et al 2003(Peng et al , 2004 and isolated cones from retinas of striped bass and ground squirrel (Rebrik et al 2000;Rebrik and Korenbrot 2004) have added significantly to our understanding of the functional properties of cone CNG channel and its modulation.…”
mentioning
confidence: 99%
“…Kalloniatis et al channels (Picco & Menini, 1993). If AGB entry occurs via cGMPgated channels, one possible reason for a lack of rod labelling is that rods and cones express different cGMP channel subunits (Hirano et al, 2000), and the effective pore size is known to be different in rods and cones (Picones & Korenbrot, 1992Picco & Menini, 1993;Stotz & Haynes, 1996). Mills and Massey (1994) reported that both type A and type B horizontal cells are localized throughout the rabbit retina, peaking at the visual streak.…”
mentioning
confidence: 99%